Enhanced carbon dioxide leads to a modified diurnal rhythm of nitrate reductase activity in older plants, and a large stimulation of nitrate reductase activity and higher levels of amino acids in young tobacco plants - Sonnewald, Uwe; et al. (Plant Cell and Environment, 1998)
Enhanced carbon dioxide led to larger increases of NR activity and NR activation, a 2-3-fold increase of glutamine, a 50% increase of glutamate, and a 2-3-fold increase in minor amino acids. It also led to a higher nitrate level. It is argued that enhanced carbon dioxide leads to a very effective stimulation of nitrate uptake, nitrate assimilation and amino acid synthesis in seedlings. This will play an important role in allowing faster growth rates in enhanced carbon dioxide at this stage.
Keywords: amino acids; elevated carbon dioxide; growth; nitrate; nitrate reductase